2013
DOI: 10.1016/j.quaint.2012.10.059
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation dynamics and their response to freshwater inflow and climate variables in the Yellow River Delta, China

Abstract: a b s t r a c tBased on SPOT Vegetation NDVI data, streamflow data and meteorological data, the variation of vegetation cover, measured by the Normalized Difference Vegetation Index (NDVI), and its response to freshwater inflow, precipitation and temperature in the Yellow River Delta and its buffer zones have been investigated for the period 1998e2009. The results show that NDVI has a remarkable regional and seasonal difference. The farther from the Yellow River Channel and the nearer to the Bohai Sea Coastlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…As one of the key components of terrestrial ecosystems, vegetation plays an important role in regulating energy exchange, the carbon cycle, and climate change through photosynthesis, surface albedo, and roughness [1,2] and is recognized as a natural linkage between the pedosphere, atmosphere, and hydrosphere of the Earth's systems [3][4][5]. Improved knowledge of vegetation variations and their relationship with climatic variables (mostly focusing on precipitation and temperature) at various spatial and temporal scales is an important and desirable goal for projecting future vegetation growth trends and their responses to climatic change [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As one of the key components of terrestrial ecosystems, vegetation plays an important role in regulating energy exchange, the carbon cycle, and climate change through photosynthesis, surface albedo, and roughness [1,2] and is recognized as a natural linkage between the pedosphere, atmosphere, and hydrosphere of the Earth's systems [3][4][5]. Improved knowledge of vegetation variations and their relationship with climatic variables (mostly focusing on precipitation and temperature) at various spatial and temporal scales is an important and desirable goal for projecting future vegetation growth trends and their responses to climatic change [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Improved knowledge of vegetation variations and their relationship with climatic variables (mostly focusing on precipitation and temperature) at various spatial and temporal scales is an important and desirable goal for projecting future vegetation growth trends and their responses to climatic change [6,7]. Recently, the response of vegetation to climate change has attracted considerable attention, particularly since the satellite-derived normalized difference vegetation index (NDVI) has been available from the early 1980s [7][8][9][10][11] and has increasingly become a hot topic in climate-change studies [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Vegetation, as an important component of terrestrial ecosystems, links pedosphere, atmosphere, and hydrosphere of the Earth's system (Salim et al 2008;Zhong et al 2010). Vegetation dynamics are highly associated with climate regimes (Piao et al 2006;Fabricante et al 2009;Meng et al 2011), and thus, land cover can serve as an ecological indicator for environmental changes at the local, regional, and global scales (Piao et al 2006;Yu et al 2006;Potter et al 2008;Salim et al 2008;Jiang et al 2013). Nemani et al (2003) estimated that water availability most strongly limits vegetation growth for over 40 % of Earth's vegetated surface, while temperature over 33 % and radiation over 27 % of Earth's vegetated surface.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in vegetation cover can also affect local, regional, and global climate through various physical, physiological, and chemical feedbacks (Kaufmann et al 2003;Suzuki et al 2007;Zhou et al 2007;Salim et al 2008;Zuo et al 2011). Vegetation dynamics and their correlations with climate variables have become one of the main themes of global change studies (Rees et al 2001;Yu et al 2006;Jiang et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…During the period from 1961 to 2010, the annual average temperature in the coastal wetlands of the Yellow River Delta increased by 1.85 • C, while the annual precipitation decreased by 121.42 mm [83]. A large number of studies have shown that over the past four decades precipitation decreased in the Yellow River Basin and the area showed a warm and dry trend [83][84][85][86]. The precipitation in the upper and middle reaches of the river has decreased due to the warm and dry regional climate.…”
Section: Climate Changementioning
confidence: 99%